Approximation of $(ψ, β)$-Differentiable Functions Defined on the Real Axis by Abel-Poisson Operators - Zhyhallo, T. V.; Kharkevych, Yu. I. (Ukrains’kyi Matematychnyi Zhurnal, 2005)
We obtain asymptotic equalities for upper bounds of approximations of functions on the classes \(\hat C_{β ,∞ }^ψ\) and \(\hat L_{β ,1}^ψ\) by Abel-Poisson operators.